Challenges of enforcement of judgments of ECOWAS community court of justice on human rights in Nigeria (2015)
The Economic Community of West African States (ECOWAS) is a sub-regional international organisation with primary aim of promoting economic Cooperation and championing the economic integration of the member states within the ECOWAS Community. The ECOWAS Community Court of Justice is a judicial organ of the ECOWAS with general jurisdictions to adjudicate on specific matters, among which is matter on human rights within the ECOWAS Community. Nigeria is one of the member States of the ECOWAS and the Community Court’s judgments are bound to be enforced in Nigeria as one of the member States. This article looks into clarification of concepts on the challenges on enforcement of the judgments of ECOWAS Community Court of justice on human rights in Nigeria. The article further considers jurisdiction of the ECOWAS Community Court of human rights on human rights in Nigeria and other community members, few Nigeria human rights cases decided in the Community Court, that relate to the challenges of enforcing the judgments of the Court, and some challenges on enforcement of the ECOWAS Community Court in Nigeria, like constitutional supremacy of the Nigerian Constitution, executive interference, corruption in the polity, technicalities of enforcing judgments, financial burden and weak measure for compliance with treaties. The way forward to the challenges on enforcement of the judgments are considered in order to proffer better solutions to the challenges